THE ETHICS OF CESAREAN SECTION ON MATERNAL REQUEST: A FEMINIST CRITIQUE OF THE AMERICAN COLLEGE OF OBSTETRICIANS AND GYNECOLOGISTS' POSITION ON PATIENT-CHOICE SURGERY - Bergeron, Veronique (Bioethics, 2007)
In recent years, the medical establishment has been speaking in favor of women's autonomy in childbirth by advocating cesarean delivery on maternal request (CDMR). This paper offers to look at the ethical dimension of CDMR through a feminist critique of the medicalization of childbirth and its influence on present-day medical ethics. I claim that the medicalization of childbirth reflects a sexist bias with regard to conceptions of the body and needs to be used with caution when applied to women's reproductive health. I then use this perspective to critically analyze the position of the American College of Obstetricians and Gynecologists (ACOG) on the ethics of decision-making in patient-choice surgery. I claim that informed consent cannot be meaningfully exercised unless women are made aware of the sexist underpinnings of the medical model of childbirth and its influence on the ethical reasoning of the American College of Obstetricians and Gynecologists. I also express concern about the effects of normalizing patient-choice cesarean sections on the choices available to pregnant women using as examples the institutional rules on mandatory cesarean sections for women with a previous cesarean delivery or breech presentation. I conclude with a call for more research into the real cost of convenience in CDMR, particularly as our increasingly strained publicly funded healthcare system would greatly benefit from the de-medicalization of normal body functions rather than an increased dependence on costly surgical technology.